Individual financial risk tolerance and the global financial crisis. (7th November 2013) - Gerrans, Paul; Faff, Robert; Hartnett, Neil; Berkman, Henk
Abstract We investigate individual investors' tolerance towards financial risk by focusing on changes associated with the global financial crisis (GFC) of 2007–2009. Financial risk tolerance (FRT) is analysed longitudinally controlling for demographic, socio‐economic and regional variations. In absolute terms, the change in FRT is small and contrasts with a popular view that risk tolerance is an elastic psychological state overly influenced by the pervading market conditions. Even in the presence of significant financial events, FRT tends to be a reasonably stable attribute in the shorter term but possibly influenced and reshaped by events more gradually over time.